Cardiometabolic Risk Factors in Adolescent Women’s Health - Marcelle Cedars (Fertility & Reproduction, 2023)
Despite significant advances in diagnosis and treatment, cardiovascular disease (CVD) remains a major cause of mortality and morbidity for men and women. While disease rates are somewhat declining for men, risk for women, and earlier age at onset, is increasing. As with many common conditions, prevention and/or early intervention for those at risk, leads to better long-term outcome than treatment and secondary prevention. In order to better achieve reduction in disease in adulthood, we need to recognize critical periods of vulnerability for disease development. These include broadly the maternal environment, but also early childhood and adolescence, two periods with rapid growth and development, where environmental “insults” may have long-lasting impact. As suggested by the Developmental Origins of Adult Disease (DoAD) and the Dutch famine studies, the in-utero environment is a critical window. And maternal health leading into pregnancy, maternal health during pregnancy and any potential environmental exposures, will all impact childhood and likely adult health. Careful studies across childhood, particularly with emphasis on BMI and BMI trajectories and adverse social situations and abuse, are producing informative data regarding the importance of this critical time-period for both awareness and intervention. And, interventions, as simple as improving diet and sleep, may improve our ability for early intervention in simple ways to improve women’s health and longevity.